Valuing the forest: willingness-to-pay for ecopark with notes on tree architecture in Ifugao, Philippines - Bimmoy, Eric D.; Bernardino, Daniel V.; Bimmoy, Sheila T. (Journal of Agriculture and Environment for International Development (JAEID), 2025)
The survey aimed to examine the factors influencing local tourists’ Willingness-To-Pay (WTP) for the ecopark, focusing on tree crown architecture and the georeferencing of indigenous trees. The study was conducted at the Ecotrail and Reservation Site of Indigenous Species (ECOTRIS) at Ifugao State University. The results revealed that ECOTRIS entails a significant consumption cost, as 90% of the tourists surveyed expressed a willingness to pay for its management. Among these, 72.2% were willing to pay ₱10, 18.5% ₱15, and 9.3% ₱20.The majority of respondents (69%) were aged 15–25 years, while 21% were 26–39 years old. The WTP results showed that ecological enhancements and approval of existing facilities were statistically significant factors. Regarding trail preferences, concreted trails were favored over unconcreted ones, with land use, situational features, and natural obstacles also influencing tourists’ willingness to pay and satisfaction with the facilities. The study found that ECOTRIS is predominantly visited by younger male tourists and university students, rather than older individuals, women, or high school students, with significant statistical differences observed among these groups. Additionally, the tree crown architecture of native trees was perceived to have higher aesthetic value compared to non-native or exotic species. Non-native species were noted to be potentially invasive, often outcompeting native trees for sunlight in forest stands.